Enabling Precision Medicine for Rare Head and Neck Tumors: The Example of BRAF/MEK Targeting in Patients With Metastatic Ameloblastoma - Brunet, Maxime; Khalifa, Emmanuel; Italiano, Antoine (Frontiers in Oncology, 2019)
Background: Ameloblastoma is a rare head and neck tumor characterized by a high incidence of BRAF mutation providing a rationale for the use of BRAF inhibitors in patients with advanced disease. Methods: We report the case of a 26-year old female presenting with metastatic ameloblastoma. A molecular screening of the tumor revealed a BRAF V600E mutation. Results: The patient started treatment with dabrafenib and trametinib and experienced complete response which is still ongoing 30 weeks after treatment onset. Conclusions: The complete response observed here illustrate the role of molecular profiling in complicate clinical situation of rare head and neck cancer and the potential benefit of BRAF-targeted therapy in ameloblastoma carrying BRAF V600E mutation.